Community experience promotes customer voice: co-creation value perspective. Issue 6 (2nd June 2021) - Yang, Bingcheng; Yu, Hongyan; Yu, Yu; Liu, Miaoling
Abstract : Purpose: Based on the online brand community, this study focuses on how online brand community experience affects customer voice and discusses the relationship between community engagement and community commitment. Specifically, we examine the mediation effect of community engagement between community experience and customer voice and also the moderation role of community commitment. Design/methodology/approach: The survey data is collected through the online survey of people who participate in the online mobile phone brand community. In total, 369 members of online community users (Huawei and Apple communities) were collected as the research samples. Then the structural equation model analysis was tested through the SPSS 25 and Mplus 7 in a two-stage analysis program. Findings: The results show that (1) customer online brand community experience has a positive impact on customer voice; (2) community engagement mediates the positive relationship between online brand community experience and customer voice; and (3) community commitment plays a moderating role between customer experience and customer voice. Compared with low level customer's community commitment, when customer's community commitment is high, the level of community engagement has a greater mediation effect on the positive relationship between community experience and customer voice. Research limitations/implications: On the one hand, the model of customer community experience to customer voice built in this paper has not been fully validated. Whether the model can get more robust results needs to be extended to more different community scenarios. On the other hand, this paper is actually cross-sectional data, which cannot strictly reveal the causal relationship. The authors recommend that future research may use other research methods to further reveal its internal mechanism. Practical implications: This paper shows that customer's community experience has an important impact on customer voice behavior. Among them, information experience and sociability remain as the important factor affecting customer voice behavior, which is quiet important for maintaining brand community and product or service improvement. Brand community managers need to consistently create multiple forms of information presentation and interaction channels to enhance the information and social experience of community members. Originality/value: First, this paper puts forward a new perspective on customer comments or feedback-customer voice, which provides a solid foundation and reference value for future scholars to explore such important phenomena. Second, the relationship between community experience and customer voice behavior was examined, which enriched the research on community experience and also discovered another positive significance of community experience in community construction. Finally, the authors examine the mediation effect of community engagement on customer voice behavior. Community engagement is one of the important indicators that reflexing community performance, which is of great significance to the brand community.